Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Active Learning Tipe Problem Solving - Abd Azis; Ma’rufah (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
Analyzing how well the Active Learning model and the Problem Solving technique enhance student learning results at MTs Al-Ishlahiyyah Tumpuk, Sambisirah, Wonorejo, Pasuruan, is the goal of this study. Students in the seventh grade served as the subjects. A qualitative approach was the methodology employed. The findings demonstrated that the application of this learning model effectively enhanced learning outcomes, with the majority of students achieving scores higher than the 75-point Minimum Completion Criteria (KKM). Some students showed strong ambition, activity, and enjoyment for the learning process, even if they were still below the Minimum Competency (KKM). According to student interviews, this methodology improved their comprehension of the subject matter, developed their capacity for original thought, and made learning more interesting and applicable. As a result, the Problem-Solving-based Active Learning paradigm has been successful in raising students' comprehension and learning abilities while fostering a more engaging and joyful learning environment. This study significantly advances the creation of creative and successful teaching strategies for classroom settings.